Ortho-vanillin derived Al(III) and Co(III) catalyst systems for switchable catalysis using ε-decalactone, phthalic anhydride and cyclohexene oxide - Diment, WT; Stößer, T; Kerr, RWF; Phanopoulos, A; Durr, CB; Williams, CK (Royal Society of Chemistry, 2021)
Switchable catalysis is a useful one-pot method to prepare block polyesters utilising a single catalyst exposed to a mixture of monomers. The catalyst is switched between lactone ring-opening polymerization (ROP) and epoxide/anhydride ring-opening copolymerization (ROCOP) by controlling its chain-end chemistry. Here, novel aluminium(III) (1) and cobalt(III) complexes (2), coordinated by ortho-vanillin derived salen ligands, show excellent switchable catalytic activity and selectivity for the preparation of poly(ε-decalactone-block-cyclohexene phthalate-block-ε-decalactone) [PDL-b-PCHPE-b-PDL]. Both complexes have competitive activities with a commercial chromium salen catalyst for epoxide/anhydride ROCOP (TOFCr(III) = 1200 h−1 vs. TOFAl(III) = 350 h−1, 1 mol% catalyst loading vs. anhydride, 100 °C) and are significantly more active than the commercial catalyst for lactone ROP (TOFcr(III) = 3 h−1 vs. TOFAl(III) = 300 h−1; 0.5 mol% catalyst loading vs. lactone, T = 100 °C). The catalysts are tolerant to low loadings (0.1 mol% vs. anhydride, 0.05% vs. lactone) and produce high molar mass triblock polyesters (Mn = 6–57 kg mol−1). The efficient production of high molar mass polyesters allows for future optimization of the block polyester thermal–mechanical properties and applications.